Medical Treatment for Postthrombotic Syndrome - Palacios, Federico Silva (Semin Intervent Radiol, 2017)
Deep vein thrombosis (DVT) is a prevalent disease. About 20 to 30% of patients with DVT will develop postthrombotic syndrome (PTS) within months after the initial diagnosis of DVT. There is no gold standard for diagnosis of PTS, but clinical signs include pitting edema, hyperpigmentation, phlebectatic crown, venous eczema, and varicose veins. Several scoring systems have been developed for diagnostic evaluation. Conservative treatment includes compression therapy, medications, lifestyle modification, and exercise. Compression therapy, the mainstay and most proven noninvasive therapy for patients with PTS, can be prescribed as compression stockings, bandaging, adjustable compression wrap devices, and intermittent pneumatic compression. Medications may be used to both prevent and treat PTS and include anticoagulation, anti-inflammatories, vasoactive drugs, antibiotics, and diuretics. Exercise, weight loss, smoking cessation, and leg elevation are also recommended. Areas of further research include the duration, compliance, and strength of compression stockings in the prevention of PTS after DVT; the use of intermittent compression devices; the optimal medical anticoagulant regimen after endovascular therapy; and the role of newer anticoagulants as anti-inflammatory agents.